The Role of Constructive Conflict Management in Fostering Team Collaboration and Innovation: A Perspective of Transformational Leadership - Badriyah, Nurul; Sulaeman, Moh. Muklis; Wibowo, Sandi Nasrudin; Anggapratama, Reza (PT. LITERASI SAINS NUSANTARA, 2024)
In rapidly changing business environments, team collaboration has become key to organizational success. Teams that can work effectively together have the potential to create innovative solutions and perform at high levels. The aim of this research is to investigate the relationship between constructive conflict management, team collaboration, and innovation, considering the influence of transformational leadership as a mediating factor. The methodology of this research is a literature review with a qualitative approach, employing descriptive analysis. Data for this study were obtained through searching articles on Google Scholar from 2006 to 2024. The findings of the study indicate that descriptive analysis regarding the role of constructive conflict management in fostering team collaboration and innovation, viewed from the perspective of transformational leadership, highlights the importance of a holistic approach in managing workplace conflicts. Constructive conflict management, involving a deep understanding of differences, identification of conflict sources, and facilitation of open discussions, plays a central role in building a work environment supportive of creativity and innovation. On the other hand, transformational leadership leads to the formation of an organizational culture that promotes individual growth and productive team collaboration.